2018
DOI: 10.1109/jtehm.2018.2866105
|View full text |Cite
|
Sign up to set email alerts
|

Design and Integration of an Inexpensive Wearable Mechanotactile Feedback System for Myoelectric Prostheses

Abstract: The aim of this paper was to demonstrate the functionality of an inexpensive mechanotactile sensory feedback system for transhumeral myoelectric prostheses. We summarize the development of a tactile-integrated prosthesis, including 1) evaluation of sensors that were retrofit onto existing commercial terminal devices; 2) design of two custom mechanotactile tactors that were integrated into a socket without compromising suction suspension; 3) design of a modular controller which translated sensor input to tactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 51 publications
0
33
1
Order By: Relevance
“…Three mechanotactile tactors integrated into the brace were aligned to stimulate the thumb, index, and middle fingers of the participant to relay tactile feedback to participants. These tactors pushed on the participant's fingers by converting rotational motion from a motor using rack and pinion gears to linear motion ( Figure 6a in Schoepp et al, 2018). The linear displacement of these actuators on the fingertips was mapped proportionally to the force sensed using force-sensitive resistor sensors that were placed on the corresponding thumb, index, and middle fingers of the prosthetic hand (Saunders and Vijayakumar, 2011).…”
Section: Tactor Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Three mechanotactile tactors integrated into the brace were aligned to stimulate the thumb, index, and middle fingers of the participant to relay tactile feedback to participants. These tactors pushed on the participant's fingers by converting rotational motion from a motor using rack and pinion gears to linear motion ( Figure 6a in Schoepp et al, 2018). The linear displacement of these actuators on the fingertips was mapped proportionally to the force sensed using force-sensitive resistor sensors that were placed on the corresponding thumb, index, and middle fingers of the prosthetic hand (Saunders and Vijayakumar, 2011).…”
Section: Tactor Setupmentioning
confidence: 99%
“…Implantable peripheral nerve interface approaches also most commonly report and utilize touch and pressure feedback corresponding to the digits (Wendelken et al, 2017;Schiefer et al, 2018;George et al, 2019). We, therefore, investigated the effect of using a mechanotactile stimulation of touch and pressure to provide the sensory information (Schoepp et al, 2018), to investigate its effect on simulated prosthesis embodiment. We found that synchronous touch and pressure stimulation evoked similar embodiment responses as brushing (no significant differences and strong positive correlation), although responses were blunted, consistent with prior literature (D'Alonzo and Cipriani, 2012).…”
Section: Passive Rhimentioning
confidence: 99%
“…FSR, as a force measuring element, offers various advantages like low-cost, small size, lightweight, robustness, and good accuracy. Also, FSR is an optimal sensor in the prosthetic application, which provides a reliable measurement of force over the existing state of sensor technologies (Schoepp et al 2018). The sensor output was applied at the analog input port of the microcontroller for getting an estimated value of prehension force during finger-object interaction.…”
Section: Tactile Sensormentioning
confidence: 99%
“…This work is licensed under a Creative Commons Attribution 4.0 License. For more information, see https://creativecommons.org/licenses/by/4.0/ sensors used in prosthetic hands are force sensitive resistors (FSRs) [10], [12], [13], piezoelectric sensors [14], [15], and capacitive sensors [16]- [18]. Capacitive sensors have good frequency response, spatial resolution, and a wide dynamic range.…”
Section: Introductionmentioning
confidence: 99%